Phosphoglucomutase Mutants of Escherichia coli K-12 - Adhya, Sankar (1971)
Bacteria with strongly depressed phosphoglucomutase (EC 2.7.5.1) activity are found among the mutants of Escherichia coli which, when grown on maltose, accumulate sufficient amylose to be detectable by iodine staining. These pgm mutants grow poorly on galactose but also accumulate amylose on this carbon source. Growth on lactose does not produce high amylose but, instead, results in the induction of the enzymes of maltose metabolism, presumably by accumulation of maltose. These facts suggest that the catabolism of glucose-1-phosphate is strongly depressed in pgm mutants, although not completely abolished. Anabolism of glucose-1-phosphate is also strongly depressed, since amino acid- or glucose-grown pgm mutants are sensitive to phage C21, indicating a deficiency in the biosynthesis of uridine diphosphoglucose or uridine diphosphogalactose, or both. All pgm mutations isolated map at about 16 min on the genetic map, between purE and the gal operon.